EVALUASI ESTETIKA LANSKAP PADA PANTAI KONDANG MERAK, DESA SUMBER BENING, KABUPATEN MALANG - Rizki Alfian; Hesti Triana; Riski Riski (Universitas Tribhuwana Tunggadewi, 2022)
Malang has many tourist attractions, such as beach tourism including Tiga Warna Beach, Batu Bengkung Beach, Goa China Beach, Banyu Anjlok Beach, Sendang Biru Beach, and Balekambang Beach (Kondang Merak Beach). The potential of existing resources and aesthetics has the effort to evaluate the landscape based on the aesthetic value of Kondang Merak Beach. This study aims to determine and assess the visual quality of the Kondang Merak Beach landscape based on the estimation of beauty value through scenic beauty estimation and recommendations for the design model of the Kondang Merak Beach tourism landscape arrangement. The estimated value of the beautiful landscape using a scale of values between 1-10. The classification of values is divided into three categories of beauty value (high, medium, and low categories. The analysis carried out by SBE value is high with a value of 50-86. Medium SBE with a value between 30-49 and low SBE with a value of 0-29. For the high-value category recommended building a gazebo along the coast. For the medium-value recommended to build a guard tower, and for the low-value recommended to make a homestay on vacant land that has not been developed/utilized.